Study of Resistivity Reduction by Annealing with a Choice of Complexing Agent in Electroless Plated Ru - Hamamura, Takanobu; Ishii, Yuko; Shimizu, Tomohiro; Ito, Takeshi; Fukumuro, Naoki; Yae, Shinji; Shingubara, Shoso (Proceedings of the IEEE International Interconnect Technology Conference, 2025)
We investigated electroless plating of Ru when using hydrazine monohydrate as a reducing agent to form low-resistivity Ru films. We compared two different complexing agents: the first is succinic acid and the second is a mixture of ammonium chloride and tartaric acid. The electrical resistivity of the electroless plated Ru film was reduced by annealing in a forming gas (N2:H2=9:1) ambient; at the same time, significant Ru crystal grain growth occurred. The results showed that the resistivity decreased from 160 to 12 μΩcm after annealing at 600 °C in the succinic acid case, whereas it decreased to 22 μΩcm when the mixture of ammonium chloride and tartaric acid was used. Thermal desorption spectroscopy analysis indicates that impurity desorption occurs more easily in the succinic acid case than in the case where the ammonium chloride and tartaric acid mixture was used.